Micro-econometric evaluation of subsidized employment in Morocco: The case of the "Idmaj" program - Abdellatif Chatri; Khadija Hadef; Naima Samoudi (Journal for Labour Market Research, 2021)
This paper aims to assess the impact of the Moroccan wage subsidy program "Idmaj". It applies the propensity score matching method to the data from a survey conducted by the Ministry of Labour on a sample of eligible individuals. Our results suggest that wage subsidies in Morocco have a positive but marginally significant effect on reducing unemployment and improving employment and a significant negative impact on wages. It also highlights some heterogeneous effects of the program, particularly on women. Finally, it appears that the program did not serve as a stepping stone to higher-paying, high-quality work and, in contrast, it had a stigmatizing effect on beneficiaries.
Keywords: C14; C31; H43; J38; J68; 330; Propensity score matching; Impact evaluation; Active labour market policy; Wage subsidies